Sistema de Dimensionamento de Pessoas e o planejamento da força de trabalho na Universidade Federal da Paraíba - Reitz, Tatiana Adriano de Oliveira (2023)
The management of available resources in public and private organizations has long been studied as a valuable and necessary practice for institutions to maintain their sustainability. In the public sphere, it is necessary for institutions to distribute available human and material resources, based on the premises of meeting institutional needs with maximum effectiveness, in the most efficient way possible. This study aims to analyze the applicability of the Personnel Dimensioning System (Sisdip) for planning the technical-administrative workforce at the Federal University of Paraíba (UFPB). The theory underlying this investigation addresses studies on planning in people management and workforce planning, consolidating the stages and planning elements applicable to Public Administration. In the same way, materials were raised that characterize the Sisdip tool and describe its functionalities. The research carried out is characterized as descriptive, exploratory, and with a qualitative approach. The method chosen was the case study, carried out through document analysis and interviews with UFPB people management agents. The interviews were developed from a semi-structured script, having been recorded and transcribed. For data analysis, the content analysis method was used. The results and discussions were divided into two parts. In the first, the most relevant issues are established with regard to planning the UFPB's technical-administrative workforce, such as: creation of courses, increased demands, turnover, existence of non-productive labor, high number of retirements and servers on permanence allowance, increase in rates of illness after the COVID19 pandemic, extinction of positions, reduction of the staff and occurrences of deviation from function. In the second part, the data and reports provided by Sisdip are described, associating this information with the existing demands in the UFPB regarding personnel planning. The research results indicate the relevance of Sisdip for planning the technical-administrative workforce at UFPB, consisting of a tool capable of processing a wide variety of data, and providing important personnel and productivity indicators. At the end, the limitations of the study and some recommendations are presented, such as the need for theoretical deepening on the theme of personnel planning, combined with initiatives from the planning and people management sectors of the UFPB, for the institutionalization of a method of technicaladministrative workforce planning at the University. Likewise, it is suggested that any planning methodology indicates which Sisdip reports and indicators will be used, and at what frequency, in order to take advantage of the facilities provided by the use of the tool. It is also proposed that further studies be carried out on the survey and analysis of qualitative issues of personnel planning, as well as the interpretation of data and the making of inferences from the data generated by Sisdip.